The influence of perceived parenting styles on socio-emotional development from pre-puberty into puberty - Ong, Min Yee; Eilander, Janna; Saw, Seang Mei; Xie, Yuhuan; Meaney, Michael J.; Broekman, Birit F. P. (European child & adolescent psychiatry, 2018)
The relative impact of parenting on socio-emotional development of children has rarely been examined in a longitudinal context. This study examined the association between perceived parenting styles and socio-emotional functioning from childhood to adolescence. We hypothesized that optimal parenting associated with improvement in socio-emotional functioning from childhood into early adulthood, especially for those with more behavioral problems in childhood. Children between ages 7 and 9 years were recruited for the Singapore Cohort Study of Risk Factors for Myopia (SCORM). Nine years later, 700 out of 1052 subjects were followed up (67%). During childhood, parents completed the Child Behavior Checklist (CBCL), while young adults completed the Youth Self-Report (YSR) and Parental Bonding Instrument (PBI). Perceived optimal parental care resulted in less internalizing and externalizing problems in early adulthood in comparison to non-optimal parental care styles. Perceived optimal paternal parenting, but not maternal parenting, in interaction with childhood externalizing problems predicted externalizing symptoms in early adulthood. No significant interactions were found between perceived parenting styles and internalizing problems. In conclusion, perceived parental care associates with the quality of socio-emotional development, while optimal parenting by the father is especially important for children with more externalizing problems in childhood.